SCHOOL LEADERSHIPS AND THEIR RELEVANCE TO MANAGEMENT: FINDINGS FROM A SYSTEMATIC LITERATURE REVIEW - Virgiawan Listanto (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2022)
Leadership has always been a topic that has attracted the attention of researchers. The purpose of this literature review research is to know the participantsâ€™ characteristics in the articles, the type of measurement, the type of school leadership and their relevance to the management. A total of 11 articles in the period 2017-2022 were used to carry out this literature review taken from the Google scholar database with the help of Harzingâ€™s Publish or Perish 8 software for data mining. The article search was done online using the keywords â€œschool leadership managementâ€. The literature review results show that the participants in this research were principals, teachers, students and family members. The setting of the studies is widely carried out in some countries, including Indonesia. The measurements used in the quantitative studies are questionnaires. However, interviews and focus group discussions were used in the qualitative approach. Most school leadership types in this literature review are instructional, transformational, and transactional. Instructional leaders were mainly focused on pedagogical issues. Meanwhile, the transformational implies mobilization and teacher participation. Moreover, transformational and transactional leadership were proven effective in conflict resolution. This show that leadership styles affect the success of school management.Â